Chromosomal Abnormalities and Hydrocephalus: Could There Be an Association between Klinefelter's Syndrome and Idiopathic Normal-Pressure Hydrocephalus? - Pesce, Alessandro; Taddei, Graziano; Palmieri, Mauro; Ciarlo, Silvia; Carnevale, Rita; Elia, Stefania; Pompucci, Angelo; Petrella, Gianpaolo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Idiopathic normal-pressure hydrocephalus shows a typical clinical triad consisting of gait disturbance, dementia, and urinary incontinence, often combined with ventriculomegaly. Fortunately, these clinical manifestations are potentially reversible by adequate surgical treatment. Men affected by Klinefelter's syndrome can present cognitive problems. These include impairments in both verbal and nonverbal memory and in executive functions, which could be related to idiopathic normal-pressure hydrocephalus in these patients. In this study, we describe the case of a 62-year-old-man genetically diagnosed with Klinefelter's syndrome with a history of gait ataxia resulting in recurrent falls. Direct associations between idiopathic normal-pressure hydrocephalus and Klinefelter's syndrome and clinical pathophysiologic and potential molecular implications are discussed.
Keywords: Klinefelter's syndrome; idiopathic normal-pressure hydrocephalus; dementia